Aging, the Great Moderation and Business-Cycle Volatility in a Life-Cycle Model - Stefan Rohrbacher; Burkhard Heer; Christian Scharrer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
According to empirical studies, the life cycle of labor supply volatility exhibits a U-shaped pattern. This may lead to the conclusion that demographic change induces a drop in output volatility. We present an overlapping generations model that replicates the empirically observed pattern and study the impact of demographic transition on output volatility. We find that the change in age-composition itself has only a marginal influence on output volatility as the mitigating effect of lower labor supply volatility is compensated by higher labor supply. Instead, the driving force behind the Great Moderation in our model is the downward shift of the age-specific labor supply volatility curve.
Keywords: J10; E32; C68; 330